2011
DOI: 10.4314/ejhd.v25i1.69839
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills of physicians during patient interaction in an in-patient setting at Tikur Anbessa Specialized Teaching Hospital (TASH), Addis Ababa, Ethiopia, 2009

Abstract: Background: Physician-patient relationship is foremost among the numerous qualities needed for sound patient care. In the Ethiopian clinical setting, a vast majority of patients complain that physicians do not interact with them properly. Objective: Assess behavior of physicians (verbal and nonverbal) when interacting with patients. Methods: Randomly selected physicians were observed in doctor-patient interactions in an inpatient setting using a standardized check list at Tikur Anbessa Hospital in November, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This was substantiated by mothers who were involved in the qualitative study expressing unhappiness that the health care providers did not understand their cultural needs. This was in line with other studies in which clients reported that their healthcare providers did not appreciate their religious or cultural needs [ 16 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was substantiated by mothers who were involved in the qualitative study expressing unhappiness that the health care providers did not understand their cultural needs. This was in line with other studies in which clients reported that their healthcare providers did not appreciate their religious or cultural needs [ 16 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study 84 % of health providers preferred universal approach of management for all women seeking maternal services regardless of their residence, socio economic status, religious background or worldview. However, a study done in Ghana indicated that as there are a range of practices imbedded in each culture, maternal care providers should never assume that all women are the same as this results in stereotyping [ 21 ]. The gap of our study with this fact might be related to lack of culturally tailored curriculum of health workers or lack of awareness of providers on the impact of culture on maternal health services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies on communication in Ethiopian health care are available in general, and in cancer care in particular [13,14]. Cancer awareness and knowledge in Ethiopia is low, especially relating to cervical cancer [15], but also regarding breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Ethiopia's undergraduate medical school curricula recently adopted the CanMEDS Framework, which identifies a physician's role as ''Communicator'' as one of the essential physician competencies. 4 Research shows that Ethiopian providers have room to grow in this area, 5 and that they rank lower than many of their African peers. 6 While several studies show Ethiopian patients are satisfied with the communication of their providers, 5,7 one study showed high levels of disrespect and abuse that was not perceived as such by patients, 8 potentially signaling that poor communication is misunderstood and underreported.…”
Section: Introductionmentioning
confidence: 99%